The effect of an enriched nutritional supplement on growth and inflammatory markers in underweight HIV-positive children aged 24-72 months - Van Niekerk, Margaret-Antoinette (Stellenbosch : Stellenbosch University, 2016)
Thesis (MNutr)--Stellenbosch University, 2016.